(untitled) (Research, Society and Development, 2023)
This study investigated the contribution of playfulness as a methodological strategy in the literacy of children in the 1st year of elementary school in remote education. Methodologically, this research is qualitative. The production (collect) of dices occurred through direct observation and informal conversations that allowed for more reliable results. The research participants were two literacy teachers who teach classes in the 1st year of elementary school. The results show that playfulness in remote teaching, from the perspective of literacy, is directly related to playing, as well as in face-to-face teaching. It is assumed that if there is an environment, interactions and pedagogically appropriate situations, children will use the language of reading and writing in ludic situations that favor the learning process. In this way, it is concluded that there is a need to offer favorable means for the development of remote classes in a way that values the condition of playfulness, since the new remote educational format presents itself as something that will remain as an educational of modern society.